The Role of Financial Management in Bringing Efficiency in Supply Chain Management - Ingrid Larasati Agustina; Esa Fauziv; Asep Anwar; Habil Slade Ogalo; Ima Ratnasari (International Journal of Supply Chain Management, 2019)
The current study is intended to examine the relationship between financial management and supply chain management. For this purpose, the links between liquidity management financing decisions, inventory management and supply chain management are explored. In addition, that, it is also explored that the inventory management mediates the relationship between liquidity management and supply chain management. The resource-based theory, free cash flow theory, and agency theory are used as base theories to develop the conceptual model. The structural equation modeling using AMOS is used to achieve the research objectives of the current study. The data is collected from the operation and finance managers of manufacturing firm operating in Indonesia. Prior to establishing direct and indirect links between variables, we have accessed the measurement of model. After establishment of model fit, the structural model is used to explain the hypothesized relationships. The direct relationship between liquidity management and supply chain management, financing decision, between inventory management, supply chain management, and between liquidity management and inventory management are significant and positive. Meanwhile, the inventory management appears as a strong mediator in the relationship between liquidity management and supply chain management. The results of the study have shown consistency with the hypothesized results. The findings of the study will be helpful for operation managers, researchers, and policy makers in understanding the relationship between financial management and supply chain management.